The peremptory influence of a uniform background for trapping neutral fermions with an inversely linear potential - De Castro, A. S. (World Scientific Publ Co Pte Ltd, 2006)
The problem of neutral fermions subject to an inversely linear potential is revisited. It is shown that an infinite set of bound-state solutions can be found on the condition that the fermion is embedded in an additional uniform background potential. An apparent paradox concerning the uncertainty principle is solved by introducing the concept of effective Compton wavelength.
Keywords: Dirac equation; pseudoscalar potential; neutral fermion